Panigloben in Homalographischer Projection - Lange, Henry, 1821-1893
This map shows the world in two circular hemispheres. Continents and some countries are labeled. Bodies of water and geographic features are marked (with relief shown by hachures). There is an ancillary map at the bottom of the page showing the North Pole, labeled "Länder um den Nord-Pol in Stereographischer Polarprojection." To either side of the ancillary map, there are colored charts comparing the heights of world mountains; they are labeled "Höhen auf der Westlichen Halbkugel" and "Höhen auf der Östlichen Halbkugel." Scale 1:94,000,000.